Castration induced circRNA expressional changes in subcutaneous adipose tissue of male pigs. (21st October 2021) - Wang, Jing; Yang, Youbing; Xing, Baosong; Chen, Junfeng; Lu, Qingxia; Zhang, Jiaqing; Ren, Qiaoling; Ma, Qiang; Guo, Hongxia; Cao, Hai
Abstract: Circular RNAs (circRNAs) participated in regulation of lipid metabolism; however, its functional role on castration‐induced lipid deposition has not been deeply researched. So in this research, we firstly compared circRNAs expressional differences in subcutaneous adipose tissue between intact and castrated male Huainan pigs. A total of 6116 differentially expressed circRNAs (DECs) were detected between these two groups (|log2 foldchange| ≥ 1 and p adj  ≤ 0.05); GO and KEGG analysis showed that their parent genes were mainly enriched in metabolism‐related pathway. And TGF‐beta, insulin, AMPK, and MAPK pathways might play vital role in castration‐induced lipid deposition. The miRNAs enriched in the constructed circRNA–miRNA network were mainly participated in adipogenesis and lipid metabolism, such as miR‐143a‐3p, miR‐378, and miR‐195. And it was verified that testosterone upregulated miR‐181a but downregulated circ_0005912 expression in a dose‐dependent manner in porcine intramuscular adipocytes, and overexpression of miR‐181a inhibited circ_0005912. Taken together, these DECs may participate in the regulation of lipid metabolism after castration by reaction with miRNAs, which indicated the novel role of circRNAs in castration‐induced lipid deposition.